ضمانات حرية الصحافة في القانون الجزائري - (:unkn) unknown (جامعة المسيلة, 2025)
The 2023 Algerian media law introduced reforms aimed at strengthening press freedom. It replaced licensing with a notification system and abolished prison sentences for publishing offenses. Legal protections for journalists and their right to source confidentiality were guaranteed. The law enforces strict professional standards and mandates employing trained journalists. However، it prohibits foreign funding and excludes dual nationals from media ownership. Despite positive aspects، vague provisions raise concerns about limiting freedoms. The law’s success ultimately depends on its fair implementation and respect for constitutional principles.
Keywords: Keywords: Media law; Freedom of the Media; Constitutional Guarantees; Regulatory Authority.